The amplifier of gang culture: prisons - Konnayil, Kevin (My University, 2025)
This paper examines how the prison system amplifies gang culture and fosters gang involvement among incarcerated individuals, particularly marginalized youth. It argues that instead of rehabilitating offenders, prisons serve as environments that facilitate gang recruitment, leading to their growth. To support this claim, three key ideas are analyzed. First, social and economic conditions drive marginalized youth towards violent behaviours and gang affiliation. Second, the prison environment exacerbates gang connections. Finally, the convergence of street and prison cultures has established a vicious cycle that deepens marginalized youth's entrenchment in gang life. The paper highlights systemic issues, such as poverty, ineffective foster care systems, and historical trauma, which create vulnerabilities that gangs take advantage of to recruit new members. This exploitation frequently happens in prisons, where gangs offer protection, identity, and economic opportunities. Additionally, the convergence between the “code of the street” and the “convict code” reinforces dangerous levels of hyper-masculinity, mistrust of authorities, and retaliatory violence. As a result, it has become a new cultural norm that sustains the cycle of gang involvement that extends far beyond incarceration. To conclude, responses from institutions have failed to disrupt this cyclical pattern. Instead, it has exacerbated it, allowing gangs to use the prison system to accelerate recruitment, thus proving how prisons no longer and have never served as a deterrent.
Keywords: gang culture; prison system; marginalized youth; gang recruitment; code of the street; convict code